Epistemology : the justification of belief - Wolfe, David L., 1939- (Downers Grove, Ill. : InterVarsity Press, 1982)
The Contours of Christian Philosophy series will consist of short introductory-level textbooks in the various fields of philosophy. These books will introduce readers to major problems and alternative ways of dealing with those problems. These books, however, will differ from most in that they will evaluate alternative viewpoints not only with regard to their general strength, but also with regard to their value in the construction of a Christian world and life view. Thus, the books will explore the implications of the various views for Christian theology as well as the implications that Christian convictions might have for the philosophical issues discussed. It is crucial that Christians attain a greater degree of philosophical awareness in order to improve the quality of general scholarship and evangelical theology.
Approaches to justification. Pure rationalism ; Immediate experience ; Reasoning from experience ; Critical interpretation ; Relativism -- The problem of criteria. The notion of "criteria" ; Criteria for truth ; The structure of warrant ; The contextual nature of testing ; The role of experience ; The status of warranted beliefs ; The problem of pluralism -- Reason and religious belief. Doubt ; Criticism and religious commitment ; The Judeo-Christian attitude toward testing ; A personal note.
Includes bibliographical references (pages 91-92).
Keywords: Knowledge, Theory of (Religion); Religion -- Philosophy